Artificial intelligence and intellectual property - Lee, Jyh-An; Hilty, Reto; Liu, Kung-Chung (Oxford University Press USA - OSO, 2021)
This edited volume provides a broad and comprehensive picture of the intersection between Artificial Intelligence technology and Intellectual Property law, covering business and the basics of AI, the interactions between AI and patent law, copyright law, and IP administration, and the legal aspects of software and data.